Gastrointestinal parasitic infections in cattle and buffaloes in southwestern region of Gujarat, India - THAKRE, BHUPENDRA KUMAR; KUMAR, BINOD; BRAHMBHATT, NILIMA; PARMAR, VIJAY L; PATEL, JAYESH; DAMOR, JAYENDRA; GAMIT, KRISHNA; PATEL, JEEMI A (The Indian Journal of Animal Sciences, 2019)
A study was conducted on cattle and buffaloes in western region of Gujarat to determine the incidence of gastrointestinal parasites (GIPs) infection in it. Coprological examination revealed, higher incidence of GIPs infections in cattle compared to buffaloes. Overall, incidence of parasitic infections in both cattle and buffaloes was recorded highest for protozoan parasites followed by nematode, trematode and least for cestode. Age wise, the highest incidence of GI parasitic infections was recorded in up to 2 years age group followed by 2–5 years aged and lowest in above 5 years aged animals. Significantly, higher prevalence of GI parasites was recorded in female cattle and buffaloes compared to male. Seasonally, significantly higher percentage of GI parasitic infections was recorded in monsoon followed by winter compared to summer. Similarly, breed wise, significantly higher infection of GI parasites was recorded in Gir cattle compared to Jaffrabadi buffaloes.